Categorizing Difference: Labor and the Colonial Experience (French Empire, First Half of the 20th Century) - Ricciardi, Ferruccio (Decentering Comparative Analysis in a Globalizing World, 2021)
Efforts to qualify labour activity in the colonial space were hampered by the plurality of labour regimes present there (from indentured labour to forced labour, subsistence labour and other forms of 'informal' work) and, moreover, by the commensurability of Eurocentric categories that were difficult to transpose across time and space, starting with that of wage labour. The case of the French Empire, in this case the territories of sub-Saharan Africa which were the subject of a regulatory effort as part of the campaigns for the abolition of slavery and forced labour from the inter-war period onwards, provides an account here of the transformations in norms and practices that are specific to colonial labour in close relationship with the metropole. In this chapter, a multiscalar analysis highlights the transnational circulation of labour control mechanisms (e.g. the work book) and means of accessing resources through work (the many forms of social protection), while also suggesting ways in which work, dependency and rights are linked and disconnected.